Adaptive seismic compression by wavelet shrinkage - Khene, M.F. (2000)
In this paper, a sophisticated adaptive seismic compression method is presented based on wavelet shrinkage. Our approach combines a time-scale transform with an adaptive non-linear statistical method. First, a discrete 2-D biorthogonal discrete wavelet transform (DWT) is applied to the multi-channel seismic signals to generate a sparse multiresolution (subband) decomposition. Compression is then achieved by shrinking the detail wavelet coefficients using a scale-dependent non-linear soft-thresholding rule. The adaptive scale-dependent thresholds are determined by minimizing the Stein's unbiased risk estimate (SURE). The proposed compression procedure is tested on marine seismic data from the Midyan basin (Red Sea, Saudi Arabia)